حملة اعلانية لشركة to - me cosmetics للتجميل - حلمان, اسيل; فنون, ايمان; النتشة, سندس; فقيات, رحاب (جامعة بوليتكنك فلسطين - تسويق الالكتروني, 2023)
The idea of the project revolves around the work team designing an advertising campaign for To-me Cosmetics, and based on the results we obtained through the market research that we conducted about To-me, we were able to identify the target groups and understand them more accurately, which helped us to know the desires, needs and interest's consumers when they make a purchase. As for the chapters of the project, they are divided into five chapters. The first chapter dealt with the pickling of the industrial sector and the cosmetic sector, describing the company and SWOT analysis, and clarifying the internal factors represented by capturing the strength and weakness of the company, and the external factors represented by opportunities and threats. As for the second chapter, we dealt with the study and analysis of the mix. Marketing, direct and indirect competitors, and electronic competitors for To-me. As for the third chapter, we discussed the market study using the questionnaire tool and defining the marketing goals of To-me. In the fourth chapter, we dealt with designing promotional ads for the company and working on analyzing them, Finally, in the fifth chapter, a website was designed for the Company.
no of pages 82, تسويق الالكتروني 2023
Keywords: الدعاية الالكترونية